129:oral What are commissioners' experiences of implementing a national programme seeking to reduce non-evidence-based healthcare in the NHS during the COVID-19 pandemic?. (28th April 2022) - Farrar, Nicola; Rooshenas, Leila; Conefrey, Carmel; Hollingworth, William; Jones, Tim; Glynn, Joel; Morley, Josie
Abstract : Objective: The impact of the COVID-19 pandemic on the English National Health Service (NHS) has been profound. Those who commission health services face questions and pressures around addressing growing waiting lists and ensuring patients receive appropriate and timely treatment. In 2019, NHS England launched the Evidence-Based Interventions (EBI) programme, a national initiative that intends to reduce provision of medical and surgical interventions found to have insufficient evidence of effectiveness - either in general, or in select patient groups. The EBI programme originally produced treatment policy recommendations for 17 interventions across several surgical specialties. Reducing provision of treatments already embedded in practice has been historically challenging for health services worldwide. Our ongoing NIHR-funded mixed methods study seeks to evaluate the impact and acceptability of the EBI programme. As part of this work, a key objective is to investigate national policy-makers' experiences of implementing the EBI programme during the COVID-19 pandemic, and its role in the COVID recovery programme. Methods: Semi-structured interviews with informants working within English Clinical Commissioning Groups (CCGs) and at a national level. Data are being analysed thematically, using the constant comparison approach. Data collection and analysis are ongoing, with 10 interviews having been undertaken with informants from 6 geographically spread CCGs. Results: Emerging findings indicate that although the pandemic impacted how informants were able to implement evidence-based treatment policies, these were perceived to be potentially useful in supporting healthcare providers to manage waiting lists in a clinically appropriate manner. Discussion: This research will provide early empirical insights into informants' experiences of priority setting during and in the wake of COVID-19. Early findings suggest that historically challenging priority setting processes may be easier to implement, from informants' perspectives, under the auspices of waiting list management following the pandemic. More developed findings and implications will be reported at the conference.